Galantamine tethered hydrogel as a novel therapeutic target for streptozotocin-induced Alzheimer's disease in Wistar rats - Manickam Rajkumar; Murugesan Sakthivel; Kottaisamy Senthilkumar; Ramasundaram Thangaraj; Soundarapandian Kannan (Elsevier, 2022)
Amyloid-β (Aβ) plaque formation, neuronal cell death, and cognitive impairment are the unique symptoms of Alzheimer's disease (AD). No single step remedy is available to treat AD, so the present study aimed to improve the drugability and minimize the abnormal behavioral and biochemical activities in streptozotocin (STZ) induced AD experimental Wistar rats. In particular, we explored the utilization of methacrylated gelatin (GelMA), which is a biopolymeric hydrogel that mimics the natural tissue environment. The synthesized biopolymeric gel contained the drug galantamine (Gal). Investigations were conducted to evaluate the behavioral activities of STZ-induced AD experimental rats under STZ ​+ ​GelMA ​+ ​Gal treatment. The experimental groups comprised the control and STZ, STZ ​+ ​GelMA, STZ ​+ ​Gal, and STZ ​+ ​GelMA ​+ ​Gal (10 ​mg/kg) treated rats. Intracerebroventricular STZ ensures cognitive decline in terms of an increase in the escape latency period, with a decrease in the spontaneous alteration of behavioral activities. Our results indicated decrease Aβ aggregation in the hydrogel-based drug treatment group and significant decreases in the levels of acetylcholinesterase and lipid peroxidation (p ​< ​0.001). In addition, the glutathione and superoxide dismutase activities appeared to be improved in the STZ ​+ ​GelMA ​+ ​Gal group compared with the other treatment groups. Furthermore, histopathological and immunohistochemical experiments showed that the GelMA ​+ ​Gal treated AD rats exhibited significantly improved behavioral and biochemical activities compared with the STZ treated AD rats. Therefore, STZ ​+ ​GelMA ​+ ​Gal administration from the pre-plaque stage may have a potential clinical application in the prevention of AD. Thus, we conclude that hydrogel-based Gal drugs are efficient at decreasing Aβ aggregation and improving the neuroinflammatory process, antioxidant activity, and neuronal growth.